Entrepreneurship dalam Mengembangkan Life Skill Santri di Pondok Pesantren Darussalam Blokagung - Muhammad Imam Ghozali (MANAGIERE: Journal of Islamic Educational Management, 2024)
Entrepreneurship is one of the important competencies that students need to have in the era of globalization. Entrepreneurship can develop students' life skills, such as the ability to think critically, creatively and innovatively, the ability to solve problems, the ability to work together and the ability to communicate. So that we can form students who have life skills and have a religious spirit with the hope that when the students leave the Islamic boarding school, these students will have strong competitiveness and ethical values ​​in society. This research is a qualitative descriptive research with a case study type. Data collection techniques used passive participant observation, semi-structured interviews and documentation. then the data analysis technique for this research uses descriptive with an interactive model of data validity using Credibility, Transferability, Dependability, Confirmability. The results of this research, Entrepreneurship Innovation in Developing the Life Skills of Santri at the Darussalam Islamic Boarding School Blokagung includes providing business units according to needs, holding training and providing coaching. Triggers for Entrepreneurship in Developing the Life Skills of Santri at the Darussalam Blokagung Islamic Boarding School include the Islamic boarding school environment and Islamic boarding school policies. Implementation of Entrepreneurship includes mentoring and coaching, direct practice, and evaluation. Entrepreneurship growth has several factors including the existence of a cohesive team, the existence of wisdom, the existence of entrepreneurship facilities, the existence of mentoring and entrepreneurship strategies.